Review on Multifunctional Nanotherapeutics for Drug Delivery, Tumor Imaging, and Selective Tumor Targeting by Hyaluronic Acid Coupled Graphene Quantum Dots - Morani, Dilip O.; Patil, Pravin O. (Current Nanoscience, 2024)
Cancer is one of the most widespread life-threatening diseases, and among different types of cancers, breast cancer is the major disease affecting many women worldwide.Background: Conventional chemotherapy using anticancer drugs has many drawbacks, like poor water solubility, poor bioavailability, rapid relapse, non-specific selectivity, effect on normal tissues, and rapid drug resistance. Thus, over the last few years, immense efforts have been made to fabricate nanotherapeutics that will release drugs in response to stimuli.Objective: Nanotherapeutics based on graphene quantum dots have been acknowledged with much gratitude in the bioscience field and investigation applications because of their distinguishing chemical and physical properties, such as medicine delivery, biosensors, and bioimaging for the advancement invention of disease.Conclusion: This paper analyzes the potential applications of graphene quantum dots for the modified and desired release of antitumor drugs. Also, it shows graphene quantum dots' capability to functionalize in the companionship of hyaluronic acid that operates regarding cancer cell directing matrix in bioimaging and multimodal therapy.
Keywords: imaging materials